Short rotation forestry : an overview of Sweden and Spain - Valerio Sardón, Pablo (SLU/Dept. of Energy and Technology, 2012)
Short rotation forestry (SRF) has got a high relevance the last decades. Fast-growing tree plantations with low rotations and high yields are expanding worldwide to meet the increasing demand of forest products. Furthermore, management of fast-growing species with energy purposes is playing an important role to accomplish bioenergy goals in the way to reduce fossil fuels consumption. This paper describes short rotation forestry aspects and its differences in Sweden and Spain, with main species and the practices used in both countries. Eucalyptus sp, Pinus radiata and Populus sp, mostly managed for pulpwood, wood-based panels and sawn products are the main species in Spain. On the other hand, Sweden is one of the leaders in Europe in willow SRF for energy, with more than 16 000 ha of willow plantations and small areas of hybrid aspen and poplar.